Impact of Marijuana Legalization on Prevalence of Maternal Marijuana Use and Perinatal Outcomes - Gnofam, Mayi; Allshouse, Amanda A.; Stickrath, Elaine H.; Metz, Torri D. (American Journal of Perinatology, 2020)
Objective We aimed to assess whether marijuana legalization was associated with a difference in prevalence of prenatal use or an increase in incidence of adverse perinatal outcomes.Study Design The present study is a retrospective cohort of September and October deliveries in the years 2012 through 2015 at a tertiary center in Colorado. Primary outcome of the study was use of marijuana, defined by self-report or biodetection. Secondary outcomes of the study included growth restriction, spontaneous preterm birth, stillbirth, preeclampsia, and neonatal or maternal death. Marijuana use prevalence was compared by year, and secondary outcomes between two periods, before and after the opening of the first recreational dispensary.Results A total of 2,392 pregnant women were included (1,165 before legalization and 1,227 after). More women used marijuana over the period of legalization (trend p = 0.01). Odds of marijuana use were higher after legalization versus before (adjusted odds ratio [aOR] = 1.8, 95% confidence interval [CI]: 1.2–2.6). Incidence of growth restriction was higher after legalization (2.9 vs. 5.1%, p = 0.0084). This difference persisted after adjustment for ethnicity and other drugs in multivariable modeling (aOR = 1.9, 95%CI: 1.2–3.0).Conclusion The prevalence of prenatal marijuana use increased over the time of legalization. Further investigation into the population impact of legalization on obstetrical outcomes is warranted given the observed increase in growth restriction.
Keywords: alcohol; cannabis; fetal growth restriction; legalization; marijuana; opioids; pregnancy; prevalence; tobacco